Angiolymphoid Hyperplasia With Eosinophilia (AHE) (Case Report) (Sirte Journal of Medical Sciences, 2022)
Angiolymphoid hyperplasia with eosinophilia is a benign proliferation of vascular channels with a surrounding infiltrate of lymphocyte and eosinophils (Du Vivier A., 2012, Mitchell and Lynch, 1996). It is rare and occurs predominantly in females in the third or fourth decade. Cases have been reported in association with arteriovenous fistulae and malformation (Bolognia et al., 2008). Clinically present with pink to red-brown, dome-shaped, dermal papules or nodules of the head or neck, especially about the ears and on the scalp (Rao BK., 1992, James et al., 2006). It may occur in the mouth, trunk, extremities, penis and vulva (James et al., 2006). Peripheral blood eosinophilia is seen in about 20% of patients (Rao BK., 1992). It is benign and spontaneous regression may occur but recurrences develop in one-third of the cases.
Keywords: Angiolymphoid; Hyperplasia; Eosinophilia; (AHE)